Modelos y teorías en la práctica de enfermería familiar y comunitaria: revisión sistemática. - Mariño Nuñez, Virginia Leonor (2025)
Introduction: Nursing models and theories have evolved significantly from the pioneering principles established by Florence Nightingale to contemporary approaches, providing essential frameworks for comprehensive health care. Understanding and applying these theoretical models is vital to address current family and social care challenges, where a holistic approach that integrates diverse theoretical perspectives is needed to meet the population's needs effectively. Objective: To analyze the application of the main nursing models and theories in family and community practice based on the available scientific evidence from 2020-2024. Methodology: The research conducted a systematic review according to the prism methodology. The researcher used databases such as Google Scholar, PubMed, Scielo, Dialnet, Elsevier, Latindex, and RedalyC. Of the 151 items identified initially, the researcher chose 32, which met specific inclusion criteria. Results: The findings showed that each model brings unique and complementary elements: Nightingale emphasizes environmental determinants, Henderson structures basic needs, Leininger incorporates cultural aspects, Orem develops self-care, King establishes mutual goals, Neuman addresses stressors, Pender promotes health, and Watson humanizes care. Interventions based on this theoretical framework helped improve professional autonomy, patient communication, self-care, and cultural skill development. Conclusion: The nursing models and theories analyzed show practical applications in family and social practice, adaptation to diverse sociocultural contexts, and providing an integrated conceptual system at the social level. Their systematic implementation significantly improves the quality of care and health outcomes.